Democratization and Clientelism : Why are Young Democracies Badly Governed? - Keefer, Philip (World Bank, Washington, DC, 2012)
This paper identifies systematic performance differences between younger and older democracies: younger democracies are more corrupt; exhibit less rule of law, lower levels of bureaucratic quality, and lower secondary school enrollments; and spend more on public investment and government workers. Only one theory explains the effects of democratic age on the wide range of policy outcomes examined here-the inability of political competitors in younger democracies to make credible promises to citizens. This explanation, first advanced in Keefer and Vlaicu (2004), offers a concrete interpretation of what political institutionalization might mean, and why it is that young democracies frequently fail to become older and well-performing democracies. A variety of tests support this explanation against alternatives. The effect of democratic age remains large even after controlling for the possibilities that voters are less well-informed in young democracies, that young democracies have systematically different political and electoral institutions, or that young democracies exhibit more polarized societies.